An Ayurvedic Approach Towards Managing Amavata Through Shodhana and Shamana Chikitsa (AYUSHDHARA, 2025)
Amavata is one among Rasapradoshaja vikara where Dushitha ama combines with Prakupita vata and later takes Sthana samshraya in Koshta, Trika and Sandhi pradesha leading to Gaatra stabdata and Sandhi vedana. The treatment modalities are based on Ama harana and Vata shamana principles. The pathogenesis and symptomology of Amavata resembles the disease Rheumatoid Arthritis (RA). Rheumatoid arthritis is an autoimmune disorder characterized by morning stiffness, swelling, pain, tenderness, and restricted movements. This condition can lead to severe consequences, including joint damage, physical disability, and hematologic abnormalities, ultimately impacting quality of life. Methodology: In the present time due to a sedentary lifestyle and stress, the incidence of Ama-related diseases is increasing. Amavata is one of the most common diseases. There is an incidence of 20-40 new cases per lakh population annually in India. Present case- A 50-year-old female patient presented with complaints of morning stiffness, associated with restricted movements, swelling, and pain in bilateral metacarpophalangeal joints, metatarsophalangeal joints, and bilateral elbow joint. She was diagnosed as a case of Amavata based on signs and symptoms along with investigations showing increased levels of inflammatory markers. The patient underwent a 45-day course of Shamana aushadhi. Later on, she was administered with Panchakarma therapies like Kshara basthi, Jambeera pinda sweda, Dhanyamladhara, etc, on an admission basis for 10 days along with Shamana aushadhi. Result: After therapies and medicines symptomatic improvement along with a substantial reduction in the levels of inflammatory markers was noted. Discussion: The treatment protocol including Shodhana and Shamana was adopted based on the Chikitsa of Amavata to avoid further progression of the disease.